Efficacy and safety of programmed cell death protein-1 inhibitor for first-line therapy of advanced gastric or gastroesophageal junction cancer: a network meta-analysis - Zhang, Yunnan; Peng, Wenxing; Yang, Wei; Zhang, Wenzhou; Fan, Yannan (Frontiers in Immunology, 2025)
BackgroundThis study conducted a network meta-analysis to evaluate and rank the safety and efficacy of programmed cell death protein-1 (PD-1) inhibitors for patients with advanced gastric or gastroesophageal junction cancer (GC/GEJC).MethodsA systematic search was conducted in PubMed, Embase, and Cochrane Library databases to compare the efficacy and safety of different treatment regimens, including overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and treatment-related adverse events (TRAEs) in patients with advanced GC/GEJC.ResultsA total of six RCT studies were ultimately included in the analysis, involving 6,294 patients. Among them, 256 patients received PD-1 inhibitor monotherapy (pembrolizumab), 3,029 patients received a PD-1 inhibitor plus chemotherapy (1,047 with pembrolizumab, 1,154 with nivolumab, 327 with sintilimab, and 501 with tislelizumab), and 3,009 received either chemotherapy or chemotherapy plus placebo. Sintilimab plus chemotherapy had the highest SUCRA value for OS (85.2%), while nivolumab plus chemotherapy had the highest SUCRA values for both PFS and ORR (96.8% and 82.9%). Four PD-1 inhibitors plus chemotherapy significantly improved median OS and ORR compared with chemotherapy. Sintilimab plus chemotherapy, pembrolizumab plus chemotherapy, and nivolumab plus chemotherapy significantly improved median PFS compared with chemotherapy. For TRAEs of grade 3 or worse, pembrolizumab monotherapy had the highest SUCRA value. Tislelizumab plus chemotherapy, as well as sintilimab plus chemotherapy, did not increase the overall incidence of TRAEs and the incidence of grade 3 or worse TRAEs.ConclusionsIn the first-line treatment of advanced GC/GEJC, PD-1 inhibitors plus chemotherapy have been demonstrated to significantly improve OS, PFS, and ORR compared with chemotherapy. Among them, sintilimab plus chemotherapy achieved the highest SUCRA value for OS, and nivolumab plus chemotherapy achieved the highest SUCRA values for PFS and ORR. Regarding safety, tislelizumab plus chemotherapy and sintilimab plus chemotherapy did not increase the overall incidence of TRAEs and the incidence of grade 3 or worse TRAEs, with good tolerability and safety.